Professionally significant psychophysiological qualities of information logical group of specialties at implementation of the experimental program of professionally applied physical training of students - Ostapenko, Y.O. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to improve vocational and applied physical training of students of economics. Material: the pedagogical study involved 72 male students (aged 19-20 years). Results: job study was conducted. Defined professionally significant neurobehavioral performance of students of information logical group. Matched professionally applied exercises for their development. The results showed that in the process of purposeful muscle activity improved mechanisms of regulation of neural processes, adaptive changes occur that affect the temporal parameters of sensorimotor motor responses. A comparative analysis of the psychophysiological indicators of students of the control and experimental groups was done. Conclusions: it was found that matched professionally applied exercises positively affect the development of psycho-physiological qualities of students information and logical group of specialties.